USABILITY TESTING WEBSITE MY UT MENGGUNAKAN METODE POST-STUDY SYSTEM USABILITY QUESTIONNAIRE BERDASARKAN PANDANGAN MAHASISWA UNIVERSITAS TERBUKA - Muhammad Yovie Ridwan; Muhamad Riyan Maulana; Dian Nurdiana (Program Studi Sistem Informasi, Universitas Banten Jaya, 2024)
Universitas Terbuka (UT) continues to strive to improve quality distance education services. As part of this effort, UT developed the Academic Information System (SIA UT) into MY UT to facilitate various student academic needs, such as academic data, curriculum, lecture schedules, exam information, study modules, academic progress, and course registration. Even though MY UT has now become an important part for students, there has been no research that evaluates its usefulness from the perspective of students as users. This research aims to test the usability level of MY UT based on the views of UT students. The method used is the Post-Study System Usability Questionnaire (PSSUQ) with four measurement scales: system usability (SysUse), information quality (InfoQual), interface quality (InterQual), and overall satisfaction (Overall). Testing was carried out by distributing questionnaires via Google Form to 100 students, consisting of 50 UPBJJ UT Serang students face-to-face and 50 students from various UPBJJs online. The research results show that the average usability score for the MY UT website is 2,049. The lowest average value on the SysUse scale is 1,938, while the highest average value is 2,120 on the InterQual scale. The InfoQual and Overall scales obtained an average value of 2,103 and 2,035 respectively. These findings indicate that although the quality of the MY UT interface is quite good, aspects of the system's usability need to be improved. It is hoped that the research results can be used for further development of MY UT to provide a better experience for users.